The internal thoughts of music students while they are performing / Marcela Maikel - Maikel, Marcela (Faculty of Music, 2015)
The purpose of this thesis is to study the internal thoughts of the music students while they are performing and how these internal thoughts will affect their performance. This study applies the quantitative method to determine the degree of internal thoughts affecting performance quality among music students. Data was collected using hand-in and online questionnaire that was answered by 40 students from four departments form Faculty of Music. The findings fall into two categories: The internal thoughts while performing and the effect of internal thoughts on the quality of students' performance. Statistical analyses reveal that the overall impact on students' internal thoughts while performing is the self confidence.